1996
DOI: 10.1007/bf02174035
|View full text |Cite
|
Sign up to set email alerts
|

Differential mRNA decay within the transfer operon of plasmid R1: identification and analysis of an intracistronic mRNA stabilizer

Abstract: Processing of the transfer operon mRNA of the conjugative resistance plasmid R1-19 results in the accumulation of stable traA mRNAs. The stable traA transcripts found in vivo have identical 3' ends within downstream traL sequences, but vary at their 5' ends. The 3' ends determined coincide with the 3' base of a predicted large clover-leaf-like RNA secondary structure. Here we demonstrate that this putative RNA structure, although part of a coding sequences, stabilizes the upstream traA mRNA very efficiently. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Our experimental setup was designed to allow induction of HSPs by heat shock and concomitant shift of groEL(Ts) cells to the restrictive temperature of 43°C (for details see Materials and Methods). For the investigation of the tra transcript levels we used a probe specific for the stable region of the tra transcript, which comprises the traA coding sequence and the 5Ј region of the traL coding region (18,21). At 22°C no conjugative DNA transfer was detectable in wildtype and groEL(Ts) cells and no traA transcripts were detectable ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Our experimental setup was designed to allow induction of HSPs by heat shock and concomitant shift of groEL(Ts) cells to the restrictive temperature of 43°C (for details see Materials and Methods). For the investigation of the tra transcript levels we used a probe specific for the stable region of the tra transcript, which comprises the traA coding sequence and the 5Ј region of the traL coding region (18,21). At 22°C no conjugative DNA transfer was detectable in wildtype and groEL(Ts) cells and no traA transcripts were detectable ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…mRNA of the 33‐kb transfer operon of plasmid R1 decays non‐uniformly [34]. Processing of the polycistronic primary transcript leads to accumulation of traA mRNA which encodes a propilin, the precursor of pilin – the major subunit of sex pili.…”
Section: The F‐like Transfer Systemsmentioning
confidence: 99%
“…traA is the second gene in the tra operon. We have observed that the traA portion of the polycistronic mRNA is particularly stable (Koraimann and Hö genauer, 1989;Koraimann et al, 1996a). Steadystate levels of traA mRNA from R1-16 can therefore be readily measured, and we have adopted this measurement as an indicator of tra operon promoter activity.…”
Section: Construction Of the Tram Mutationsmentioning
confidence: 99%
“…Quantification of several mRNA species at the same time was performed as described previously (Koraimann et al, 1996a) according to O'Donovan et al (1991). Four oligonucleotides were used; the first one, designated TRAA2, was complementary to the traA mRNA.…”
Section: Rna-oligonucleotide Protection Experimentsmentioning
confidence: 99%